Self-repairable epoxy heat-conducting structural adhesive
By using epoxy-terminally modified polysulfide rubber and thiol-terminally modified epoxy resin combined with small molecule tertiary amine self-repair promoters in thermally conductive structural glue, the self-repair ability of thermally conductive structural glue is achieved, solving the problem of The problem of thermally conductive structural adhesives in the prior art is prone to breakage, high shear strength and thermal conductivity are maintained, and service life is extended.
Patent Information
- Application Number
- CN202411376121.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The existing thermally conductive structural adhesives are prone to cracks and breaks under stress and aging, resulting in failure of the packaging system and lack of self-repair capabilities, which increases the maintenance cost and difficulty of re-coating.
Using a self-repairable epoxy thermal conductivity adhesive, a three-dimensional web-shaped web-shaped by combining epoxy-based end-modified polysulfide rubber, thiol-based end-modified epoxy resin and small molecule tertiary amine self-healing accelerator. Structural and dynamic exchange reactions to achieve self-healing of colloids.
This thermally conductive structural adhesive can be self-repaired after breaking, maintaining high shear strength and thermal conductivity, extending service life, avoiding the need for re-coating, and reducing maintenance costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of structural adhesives, and particularly relates to a self-repairable epoxy-type thermally conductive structural adhesive. Background Art
[0002] Thermally conductive structural adhesive is a material that has thermal conductivity and can withstand static and dynamic loads after curing. It is specially used for bonding rigid structural components that require thermal conductivity. Different from the quick-bonding "self-adhesive" characteristics of pressure-sensitive adhesives, and also different from the focus of sealants on flexibility and sealing capabilities under various conditions, since the bonded parts need to maintain high structural strength, structural adhesives as connecting materials should have high modulus. Traditional fuel vehicles are gradually replaced by new energy vehicles, and the increasing popularity of new energy vehicles in the market has led to more attention for power batteries. Structural adhesives for power batteries need to take into account both high-strength bonding and suitable thermal conductivity. Although thermally conductive structural adhesives currently have good shear strength and thermal conductivity, in order to further meet the comprehensive requirements of their process requirements and application performance, their optimization and iteration work is ongoing. For example, patent CN 115418187 A adds polythiols, thermal conductive agents and other auxiliary agents to the epoxy thermal conductive structural adhesive formula, which prolongs the operating time and greatly improves its thermal conductivity. Patent CN 117683502 A adds silane-terminated polyether components to the thermal conductive adhesive formula, which improves the flexibility of the thermal conductive adhesive and increases the elongation at break to 60%. However, during use, due to stress, aging and other factors, once the colloid cracks and expands until it breaks, it will cause the entire packaging system and even the entire battery pack to fail. Re-coating involves problems such as difficulty in removing residual glue and high maintenance costs.
[0003] Structural materials with self-healing properties are an effective way to solve the above problems. Microcracks may be generated in the process of using structural adhesives under stress and aging environment. The further expansion of microcracks will lead to the final fracture of the adhesive surface and bonding failure. At present, there are reports that sealants and pressure-sensitive adhesives have self-healing properties, but they are all about some self-healing materials and low-shear adhesives without fillers.
[0004] Compared with the low shear strength and low rigidity of sealants and pressure-sensitive adhesives, thermally conductive structural adhesives are difficult to self-repair due to their high shear strength and high rigidity. At the same time, since thermally conductive structural adhesives require the addition of a large amount of thermally conductive fillers to provide thermal conductivity, the difficulty of self-repair is further increased. Therefore, there is no self-repairable thermally conductive structural adhesive in conventional technologies. Summary of the invention
[0005] The purpose of the present invention is to provide a self-repairable epoxy thermal conductive structural adhesive, the self-repairing technology of which can solve the problem that the existing thermal conductive structural adhesive needs to be re-coated after failure due to fracture.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A self-repairable epoxy thermal conductive structural adhesive comprises component A, component B and component C, which are calculated by weight as follows:
[0008] Component A: 20-40 parts of epoxy-terminated modified polysulfide rubber;
[0009] 3-15 parts of flexible epoxy resin;
[0010] 16 to 39 parts of thermal conductive filler;
[0011] Component B: 15-25 parts of mercapto-terminated modified epoxy resin;
[0012] Component C: 12 to 36 parts of amine polymer curing agent;
[0013] 0.33 to 1 part of self-repair accelerator.
[0014] The epoxy-terminated modified polysulfide rubber comprises 28-220 parts of polysulfide rubber and 100 parts of bisphenol A or F-type epoxy resin by weight. Under the protection of an inert atmosphere, the epoxy-terminated modified polysulfide rubber having an epoxy equivalent of 300-550 g / eq is subjected to an addition reaction at 75-85° C. for 2-6 hours, wherein the disulfide bond content is 8-25%.
[0015] The polysulfide rubber is a diethyl type terminal mercapto polysulfide, and the structural formula is: HS (RSS) m RSH; wherein: R is -C2H4-O-CH2O-C2H4-; the value of m is such that the average molecular weight of the diethyl type terminal mercapto polysulfide is 1000 to 7500, and the mercapto content is 1.1 to 2.0%;
[0016] Furthermore, the polysulfide rubber is preferably one or more of LP55, LP32, JLY124, and JLY155.
[0017] The epoxy equivalent of the bisphenol A or F type epoxy resin is 150 to 230 g / eq;
[0018] Furthermore, the bisphenol A or F type epoxy resin is preferably one or more of: E-51, E-44, E-55, NPEL-127E, NPEL-128E, NPEF-170.
[0019] The thiol-terminated modified epoxy resin is prepared by adding 35-75 parts of a small molecule organic dithiol and 100 parts of a bisphenol A or F type epoxy resin under an inert atmosphere for an addition reaction at 70-90° C. for 2-6 hours to obtain a thiol-terminated modified epoxy resin having a thiol content of 1.1-6.4%.
[0020] The ratio of the molar number of mercapto groups in the mercapto-terminated modified epoxy resin to the molar number of disulfide bonds in the epoxy-terminated modified polysulfide rubber is 1:(2.8-3.6);
[0021] The relative molecular mass of the small molecule organic dithiol is 90 to 200;
[0022] The small molecule organic dithiol is one of alkyl dithiol, dithiol alkyl sulfide, oxaalkyl dithiol, alicyclic alkyl dithiol or aromatic cycloalkyl dithiol;
[0023] Furthermore, the small molecule organic dithiol is preferably one or more of 1,2-ethanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 3,6-dioxa-1,8-octanedithiol, and dithiol diethyl sulfide;
[0024] The epoxy equivalent of the bisphenol A or F epoxy resin is 150 to 230 g / eq.
[0025] Furthermore, the bisphenol A or F type epoxy resin is preferably one or more of: E-51, E-44, E-55, NPEL-127E, NPEL-128E, NPEF-170.
[0026] The pKa value of the self-repairing accelerator should be greater than 10, and small molecule tertiary amines are selected, such as N-methyldiethanolamine (MDEA), tetramethylguanidine, triethylamine, and 1,8-diazabicyclo[5,4,0]undec-7-ene (DBU);
[0027] Furthermore, the small molecule tertiary amine self-repair promoter is preferably 1,8-diazabicyclo[5,4,0]undec-7-ene (DBU) or N-methyldiethanolamine (MDEA).
[0028] The flexible epoxy resin is one or more of dimer acid modified epoxy resin, polyurethane modified epoxy resin, and polyether modified epoxy resin;
[0029] Furthermore, the flexible epoxy resin is preferably one or more of DER-791, DER-852, DER-858, EPCO-1105, and XA-406T.
[0030] The thermal conductive filler is one or more of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, spherical boron nitride, and spherical alumina;
[0031] Furthermore, the thermally conductive filler is preferably one or more of hexagonal boron nitride, cubic boron nitride, and spherical boron nitride.
[0032] The amine polymer curing agent is one or more of a polyamide curing agent, a polyetheramine curing agent, a fatty amine polymer curing agent, an alicyclic amine polymer curing agent, and an aromatic amine polymer curing agent;
[0033] Furthermore, the amine polymer curing agent is preferably one or more of: JH-5140, JH-5150, JH-5300E, and GPM-800.
[0034] A method for preparing a self-repairable epoxy thermally conductive structural adhesive is as follows:
[0035] (1) mixing epoxy-terminated modified polysulfide rubber and flexible modified epoxy resin uniformly, adding thermal conductive filler and dispersing them uniformly to prepare component A;
[0036] (2) mixing an amine polymer curing agent and a small molecule tertiary amine self-healing accelerator uniformly to prepare a C component;
[0037] (3) Component A, component B, and component C are uniformly mixed and cured at 20-30° C. and 0.09-0.11 MPa for 72-168 h to obtain a self-healing epoxy thermal conductive structural adhesive; wherein the sum of the molar number of epoxy groups in component A and the molar number of hydroxyl groups in component B is equal to the molar number of active hydrogen in the amine polymer curing agent in component C.
[0038] A self-repairing method for a self-repairable epoxy thermally conductive structural adhesive, wherein the self-repairable thiol-modified epoxy thermally conductive structural adhesive is maintained at 60-80°C and 0.1-0.5MPa pressure for 20-40min after curing to achieve self-repairing; the conditions are preferably maintained at 70°C and 0.1MPa pressure for 30min.
[0039] The self-repairing mechanism of the epoxy thermal conductive structural adhesive of the present invention is:
[0040] The epoxy groups and amine groups in the self-healing epoxy thermal conductive structural adhesive component are cured to form a three-dimensional network structure, ensuring that the shear strength and rigidity of the thermal conductive structural adhesive can meet the use requirements; at the same time, after the colloid breaks, under the strong alkaline conditions provided by hot pressing and small molecule tertiary amine self-healing promoters, the thiol groups in the thiol-terminated modified epoxy resin and the disulfide bonds in the epoxy-terminated modified polysulfide rubber are dynamically exchanged, so that the network structure is recombined to achieve self-repair of the colloid; the flexibility of the flexible epoxy resin molecular chain can increase the contact area of the broken adhesive surface, solving the influence of thermal conductive fillers on self-repair.
[0041] Compared with the prior art, the present invention has the following advantages:
[0042] 1. The present invention provides a self-repairable epoxy thermally conductive structural adhesive, which has an increased self-repairing function while ensuring that other properties of the thermally conductive structural adhesive are not affected, and has broad prospects and important significance in expanding the scope of use and application of the thermally conductive structural adhesive.
[0043] 2. The self-repairable epoxy thermally conductive structural adhesive provided in each embodiment of the present invention is characterized in that it has a new repair capability after fracture while ensuring that the high shear strength and good thermal conductivity of the thermally conductive structural adhesive are not affected. After being applied to a power battery, it can be repaired when the colloid is broken to avoid re-coating.
[0044] 3. The self-repairable epoxy thermally conductive structural adhesive of each embodiment of the present invention has an epoxy group and an amine group that are cured to form a three-dimensional network structure, which ensures that the shear strength and rigidity of the thermally conductive structural adhesive can meet the use requirements; the strong alkaline conditions provided by the small molecule tertiary amine self-repairing promoter can promote the dynamic exchange of the thiol groups in the thiol-terminated modified epoxy resin and the disulfide bonds in the epoxy-terminated modified polysulfide rubber under hot pressing conditions after the colloid breaks, so that the network structure is recombined, thereby realizing the self-repair of the colloid; the flexibility of the flexible epoxy resin molecular chain can increase the contact area of the broken adhesive surface and reduce the influence of the thermally conductive filler on the self-repair. Therefore, the combination of the specific components and specific amounts of the epoxy thermally conductive structural adhesive in the embodiment of the present invention can realize the self-repair function. DETAILED DESCRIPTION
[0045] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0046] The present invention is specifically explained below in conjunction with the examples. The raw materials used in the examples and comparative examples are all commercially available and are not particularly limited in the present invention.
[0047] The following Preparation Examples 1 to 2 are for synthesizing epoxy-terminated modified polysulfide rubber for use in the examples, Preparation Example 3 is for synthesizing epoxy-terminated modified polysulfide rubber for use in Comparative Example 5, Preparation Examples 4 to 5 are for synthesizing mercapto-terminated modified epoxy resins for use in the examples, and Preparation Example 6 is for synthesizing mercapto-terminated modified epoxy resins for use in Comparative Example 6.
[0048] Preparation Example 1
[0049] 100 g of epoxy resin NPEF170 and 100 g of polysulfide rubber JLY155 were weighed; under the protection of an inert atmosphere, an addition reaction was carried out at 80° C. for 2 h to obtain an epoxy-terminated modified polysulfide rubber ELP-1 with an epoxy equivalent of 338 g / eq and a disulfide bond content of 18%.
[0050] Preparation Example 2
[0051] 100 g of epoxy resin NPEF170 and 150 g of polysulfide rubber JLY155 were weighed; under the protection of an inert atmosphere, an addition reaction was carried out at 80° C. for 2 h to obtain epoxy-terminated modified polysulfide rubber ELP-2 with an epoxy equivalent of 435 g / eq and a disulfide bond content of 22%.
[0052] Preparation Example 3
[0053] 100 g of epoxy resin NPEF170 and 200 g of polysulfide rubber JLY155 were weighed; under the protection of an inert atmosphere, addition reaction was carried out at 80° C. for 2 h to obtain epoxy-terminated modified polysulfide rubber ELP-3 with an epoxy equivalent of 645 g / eq and a disulfide bond content of 25%.
[0054] Preparation Example 4
[0055] 100 g of epoxy resin E-44 and 40 g of 1,6-hexanedithiol were weighed; under the protection of an inert atmosphere, an addition reaction was carried out at 80° C. for 2 h to obtain a thiol-terminated modified epoxy resin ESH-1 having a thiol content of 2.2%.
[0056] Preparation Example 5
[0057] 100 g of epoxy resin NPEF170 and 60 g of 1,6-hexanedithiol were weighed; under the protection of an inert atmosphere, an addition reaction was carried out at 80° C. for 2 h to obtain a thiol-terminated modified epoxy resin ESH-2 having a thiol content of 3.3%.
[0058] Preparation Example 6
[0059] 100 g of epoxy resin NPEF170 and 48 g of 1,6-hexanedithiol were weighed; under the protection of an inert atmosphere, an addition reaction was carried out at 80° C. for 2 h to obtain a thiol-terminated modified epoxy resin ESH-3 having a thiol content of 0.3%.
[0060] The epoxy-terminated modified polysulfide rubber obtained in Preparation Examples 1 to 2 and the mercapto-terminated modified epoxy resins of Preparation Examples 4 to 5 are respectively used to form the preparation of the self-repairable epoxy-type thermally conductive structural adhesives of Examples 1 to 3. Comparative Example 1 does not contain a small molecule tertiary amine self-repairing promoter, Comparative Example 2 replaces the epoxy-terminated modified polysulfide rubber with epoxy resin E51, and Comparative Example 3 does not contain a mercapto-terminated modified epoxy resin. Comparative Example 4 replaces the small molecule tertiary amine self-repairing promoter with polyethylene polyamine. Comparative Example 5 replaces the epoxy-terminated modified polysulfide rubber ELP-3 whose epoxy equivalent is not within the specified range with the epoxy-terminated modified polysulfide rubber ELP-1. Comparative Example 6 replaces the mercapto-terminated modified epoxy resin ESH-3 whose mercapto content is not within the specified range with the mercapto-terminated modified epoxy resin ESH-1.
[0061] Example 1
[0062] Component A: Weigh 20g of epoxy-terminated modified polysulfide rubber ELP-1 and 6g of flexible epoxy resin EPCO-1105, mix well, add 18.4g of thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0063] Component B: 15g mercapto-terminated modified epoxy resin ESH-1;
[0064] Component C: 13.8g amine polymer curing agent JH-5140;
[0065] 0.41g small molecule tertiary amine self-healing promoter DBU.
[0066] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain a self-repairable epoxy thermally conductive structural adhesive.
[0067] Example 2
[0068] Component A: weigh 20g epoxy-terminated modified polysulfide rubber ELP-2 and 6g flexible epoxy resin EPCO-1105, mix well, add 17.8g thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0069] Component B: 15g mercapto-terminated modified epoxy resin ESH-1;
[0070] Component C: 12g amine polymer curing agent JH-5140;
[0071] 0.41g small molecule tertiary amine self-healing promoter DBU.
[0072] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain a self-repairable epoxy thermally conductive structural adhesive.
[0073] Example 3
[0074] Component A: Weigh 20g of epoxy-terminated modified polysulfide rubber ELP-1 and 6g of flexible epoxy resin EPCO-1105, mix well, add 18.8g of thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0075] Component B: 15g mercapto-terminated modified epoxy resin ESH-2;
[0076] Component C: 14.9g amine polymer curing agent JH-5140;
[0077] 0.41g small molecule tertiary amine self-healing promoter DBU.
[0078] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain a self-repairable epoxy thermally conductive structural adhesive.
[0079] Comparative Example 1
[0080] The difference from Example 1 is that it does not contain the small molecule tertiary amine self-repairing accelerator DBU, specifically:
[0081] Component A: Weigh 20g of epoxy-terminated modified polysulfide rubber ELP-1 and 6g of flexible epoxy resin EPCO-1105, mix well, add 18.4g of thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0082] Component B: 15g mercapto-terminated modified epoxy resin ESH-1;
[0083] Component C: 13.8g amine polymer curing agent JH-5140.
[0084] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0085] Comparative Example 2
[0086] The difference from Example 1 is that epoxy resin E51 replaces epoxy-terminated modified polysulfide rubber ELP-1, specifically:
[0087] Component A: Weigh 20g epoxy resin E51 and 6g flexible epoxy resin EPCO-1105, mix well, add 18.4g thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0088] Component B: 15g mercapto-terminated modified epoxy resin ESH-1;
[0089] Component C: 13.8g amine polymer curing agent JH-5140;
[0090] 0.41g small molecule tertiary amine self-healing promoter DBU.
[0091] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0092] Comparative Example 3
[0093] The difference from Example 1 is that it does not contain mercapto-terminated modified epoxy resin, specifically:
[0094] Component A: Weigh 20g epoxy-terminated modified polysulfide rubber ELP-1 and 6g flexible epoxy resin EPCO-1105, mix well, add 11.2g thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0095] Component B: 7.2g amine polymer curing agent JH-5140;
[0096] 0.26g small molecule tertiary amine self-healing accelerator DBU.
[0097] Component A and component B were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0098] Comparative Example 4
[0099] The difference from Example 1 is that polyethylene polyamine replaces the small molecule tertiary amine self-repairing accelerator DBU, specifically:
[0100] Component A: Weigh 20g of epoxy-terminated modified polysulfide rubber ELP-1 and 6g of flexible epoxy resin EPCO-1105, mix well, add 18.4g of thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0101] Component B: 15g mercapto-terminated modified epoxy resin ESH-1;
[0102] Component C: 13.8g amine polymer curing agent JH-5140;
[0103] 0.41g polyethylene polyamine.
[0104] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0105] Comparative Example 5
[0106] The difference from Example 1 is that the epoxy-terminated modified polysulfide rubber ELP-3 replaces the epoxy-terminated modified polysulfide rubber ELP-1, specifically:
[0107] Component A: Weigh 20g epoxy-terminated modified polysulfide rubber ELP-3 and 6g flexible epoxy resin EPCO-1105, mix well, add 18.4g thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0108] Component B: 15g mercapto-terminated modified epoxy resin ESH-1;
[0109] Component C: 13.8g amine polymer curing agent JH-5140;
[0110] 0.41g small molecule tertiary amine self-healing promoter DBU.
[0111] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0112] Comparative Example 6
[0113] The difference from Example 1 is that the thiol-terminated modified epoxy resin ESH-3 replaces the thiol-terminated modified epoxy resin ESH-1, specifically:
[0114] Component A: Weigh 20g of epoxy-terminated modified polysulfide rubber ELP-1 and 6g of flexible epoxy resin EPCO-1105, mix well, add 18.4g of thermal conductive filler BN-SS and disperse at 1200rpm, 25℃, 0.1MPa for 20min;
[0115] Component B: 15g mercapto-terminated modified epoxy resin ESH-3;
[0116] Component C: 13.8g amine polymer curing agent JH-5140;
[0117] 0.41g small molecule tertiary amine self-healing promoter DBU.
[0118] Component A, component B, and component C were mixed evenly, and cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0119] The epoxy thermal conductive structural adhesives of the above embodiments and comparative examples were subjected to performance tests, and the test methods are as follows:
[0120] 1.Tensile strength and modulus test
[0121] GB / T 1040-2006 was used for the test. Specimens with length, width and thickness of 150mm, 10mm and 2mm were prepared. After 7 days of room temperature curing, three specimens were tested at a test speed of 5mm / min as required by the standard. The test was stopped when the specimen broke. The tensile force was recorded, the tensile strength and modulus were calculated, and the average of the test results of the three specimens was taken.
[0122] Table 1 Tensile strength test results
[0123]
[0124] 2. Shear strength test
[0125] The heat-conductive structural adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were coated on the ends of the corona-treated aluminum plates, and the coated surfaces were overlapped. The overlap area was about 25 mm*13 mm. The aluminum plates were cured at 25°C and 0.1 MPa for 96 hours to obtain the aluminum plates with the ends bonded.
[0126] In order to effectively test and calculate the self-healing ability, the bonded aluminum plates were subjected to a shear strength test. The test method was measured according to the standard GB / T 7124-2008 method, and the shear strength S1 was recorded. The aluminum plates with residual glue after the first test were placed face to face, and self-healed at 70°C and 0.1MPa for 30 minutes. After that, they were taken out and cooled to room temperature for a shear strength test, and the shear strength S2 was recorded. The healing efficiency was calculated by the ratio of S2 to S1, and the results are shown in Table 1.
[0127] Table 2 Shear strength test results before and after self-repair
[0128]
[0129]
[0130] 3. Thermal conductivity test
[0131] Use hotdisk to test in accordance with the international standard ISO 22007-2. The length and width of the sample block is greater than 20mm*20mm, and the thickness is greater than 3mm. Three samples are tested each time for thermal conductivity test. After the test, the sample block is cut into two pieces horizontally from the side and the cross sections are overlapped together. Self-repair is achieved at 70℃ and 0.1MPa for 30 minutes. Then the thermal conductivity test is carried out after it is taken out and cooled to room temperature.
[0132] Table 3 Thermal conductivity test results before and after self-repair
[0133]
[0134] As can be seen from Table 1, the thermal conductive structural adhesive has high tensile strength and modulus, and thus can provide sufficient strength and rigidity to avoid significant deformation when subjected to external impact, thereby affecting use.
[0135] As can be seen from Table 2 and Table 3, in Examples 1 to 3, epoxy-terminated polysulfide rubber was used in combination with mercapto-terminated modified epoxy resin and self-healing accelerator. After the colloid was broken, it could be self-repaired under the strong alkaline conditions provided by the self-repairing accelerator, and the healing rate reached more than 80%. The shear strength and thermal conductivity after healing could meet the use requirements. In Comparative Example 1, since no self-repairing accelerator was used, strong alkaline conditions could not be provided. Although the exchange between disulfide bonds occurred to a certain extent, it was difficult, so the healing rate was low. In Comparative Example 2, epoxy-terminated modified polysulfide rubber was not used, and the dynamic exchange between disulfide bonds and sulfhydryl groups could not be achieved, so self-healing was impossible. In Comparative Example 3, no sulfhydryl-terminated modified epoxy resin was used, and no sulfhydryl group was provided. The disulfide exchange efficiency was lower than that of thiol-disulfide exchange, so although it could be healed, the degree was not high. The polyethylene polyamine accelerator pKa <10 used in Comparative Example 4 did not provide enough alkaline conditions, so the healing rate was low. Comparative Example 5 uses epoxy-terminated modified polysulfide rubber ELP-3, which has fewer epoxy groups and more disulfide bonds. Although the healing rate and thermal conductivity after healing are both high, the shear strength before and after healing is very low, which does not meet the requirements for structural adhesive use. Comparative Example 6 uses thiol-terminated modified epoxy resin ESH-3, which has a reduced thiol content and a reduced number of effective components capable of self-repair, so the healing rate is low.
[0136] It can be seen that the self-repairable epoxy thermally conductive structural adhesive of the embodiment of the present invention has high tensile strength and modulus, wherein the epoxy-terminated modified polysulfide rubber and the mercapto-terminated modified epoxy resin components not only ensure the high bonding ability of the structural adhesive through cross-linking reaction, but also can give the thermally conductive structural adhesive the ability to self-repair through the dynamic exchange reaction of disulfide bonds-thiol groups under the strong alkaline conditions provided by the self-repairing promoter, so that the thermally conductive structural adhesive has good shear bonding and extends its service life through self-repair. The omission or replacement of any component will significantly affect the self-repairability of the epoxy thermally conductive structural adhesive. Therefore, the combination of specific components of the epoxy thermally conductive structural adhesive of the embodiment of the present invention can achieve the self-repairing function.
[0137] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A self-repairable epoxy thermally conductive structural adhesive, characterized in that: Including component A, component B and component C, calculated by mass: Component A: 20-40 parts of epoxy-terminated modified polysulfide rubber; 3-15 parts of flexible epoxy resin; 16 to 39 parts of thermal conductive filler; Component B: 15-25 parts of mercapto-terminated modified epoxy resin; Component C: 12 to 36 parts of amine polymer curing agent; 0.33 to 1 part of self-repair accelerator.
2. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The self-repairing accelerator is one of N-methyldiethanolamine (MDEA), tetramethylguanidine, triethylamine, and 1,8-diazabicyclo[5,4,0]undec-7-ene (DBU).
3. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The epoxy equivalent of the epoxy-terminated modified polysulfide rubber is 300-550 g / eq, and the disulfide bond content is 8-25%.
4. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The mercapto content in the mercapto-terminated modified epoxy resin is 1.1-6.4%.
5. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The flexible epoxy resin is one or more of dimer acid modified epoxy resin, polyurethane modified epoxy resin and polyether modified epoxy resin.
6. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The thermal conductive filler is one or more of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, spherical boron nitride and spherical alumina.
7. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The amine polymer curing agent is one or more of a polyamide curing agent, a polyetheramine curing agent, a fatty amine polymer curing agent, an alicyclic amine polymer curing agent, and an aromatic amine polymer curing agent.
8. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The epoxy-terminated modified polysulfide rubber is obtained by subjecting polysulfide rubber and bisphenol A or F type epoxy resin to an addition reaction at 75-85° C. for 2-6 hours under the protection of an inert atmosphere.
9. The self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The mercapto-terminated modified epoxy resin is obtained by addition reaction of small molecule organic dithiol and bisphenol A or F type epoxy resin at 70-90° C. for 2-6 hours under the protection of inert atmosphere.
10. A self-repairing method for the self-repairable epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The cured epoxy thermal conductive structural adhesive is kept at 60-80°C and 0.1-0.5MPa for 20-40 minutes to achieve self-repair.
